Usability Evaluation and Alternative Interface Design Recommendations for the GoFood Merchant Application - Saputro, Singgih Rochmad; Santoso, Harry Budi (Indonesian Scientific Journal, 2026)
The GoFood Merchant application serves as a critical platform for merchant onboarding and product activation within Indonesia’s digital food delivery ecosystem. Despite its key role, user feedback indicates persistent usability issues, particularly in corporate onboarding. This study evaluated and improved the usability of GoFood Merchant by focusing on workflow complexity, information clarity, and interface consistency. A mixed-methods exploratory case study was conducted involving quantitative and qualitative data collected from merchant owners, merchant staff, and IT experts. Quantitative data were obtained using the system usability scale (SUS) questionnaire, while qualitative data were collected through task-based usability testing, open-ended questions, and an evaluation based on heuristic design principles derived from Shneiderman’s eight golden rules of interface design. The initial evaluation of the existing (“as-is”) interface yielded an SUS score of 63.83, indicating usability below the accepted benchmark, and revealed 10 consensus usability issues related to complex task flow, unclear system feedback, and inconsistent interface elements. Based on these findings, a redesign was developed using user-centered design (UCD) principles through iterative low-fidelity and high-fidelity prototyping. The redesigned (“to-be”) prototype was subsequently evaluated using the same instruments. Usability was significantly improved, with an SUS score of 85 and average principle-based evaluation ratings above 4.0 across all interface design principles derived from Shneiderman’s eight golden rules. These findings demonstrate that systematic usability evaluation combined with iterative UCD-based redesign can effectively enhance user satisfaction, efficiency, and comprehension in complex onboarding systems. This study provides validated design recommendations for improving GoFood Merchant onboarding and contributes empirical evidence for usability-driven interface redesign in large-scale mobile platforms.